1994
DOI: 10.1007/bf02767728
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of plasma free amino acids in nephrotic syndrome

Abstract: In order to assess the plasma amino acid pattern in nephrotics, we studied 19 nephrotic patients in good general and nutritional conditions. The results were compared with those of 8 healthy controls of matched age and sex. A highly significant rise of plasma glutamic acid and hydroxyproline was detected in nephrotics. When the latter group is divided into 2 subgroups according to the serum creatinine level, the rise in plasma values of both amino acids was detected in both subgroups compared to the controls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…Similar to what has been described in other studies of human CKD, dogs with PLN had significantly lower leucine, tyrosine, and threonine concentrations, as compared to healthy controls . However, there were several dissimilarities between our findings and these studies, as well as people with nephrotic syndrome in which there are significantly higher concentrations of NEAA, glutamic acid, hydroxyproline and alanine . In people with CKD, low histidine concentrations are associated with PEW, inflammation, oxidative stress, and decreased survival …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to what has been described in other studies of human CKD, dogs with PLN had significantly lower leucine, tyrosine, and threonine concentrations, as compared to healthy controls . However, there were several dissimilarities between our findings and these studies, as well as people with nephrotic syndrome in which there are significantly higher concentrations of NEAA, glutamic acid, hydroxyproline and alanine . In people with CKD, low histidine concentrations are associated with PEW, inflammation, oxidative stress, and decreased survival …”
Section: Discussionsupporting
confidence: 87%
“…Without adequate concentrations of EAA, animals cannot meet physiologic demands for protein synthesis, thus contributing to decreased albumin concentrations, impaired immune function, and loss of lean muscle mass. In addition to measuring absolute plasma concentrations, ratios comparing EAA and NEAA have been used in people to assess AA status . The alterations in AA in CKD are because of alterations in nitrogen metabolism, tubular filtration, reabsorption, and excretion as well as increased inflammation …”
Section: Introductionmentioning
confidence: 99%
“…The kidneys have a vital role in homeostasis, metabolism, and regulation of the serum concentration of amino acids. Glutamic acid is one of them, and it is correlated with kidney production as well as the accumulation as a result of decreased renal uptake [ 43 , 44 , 45 ]. In human medicine it was increased in patients with normal serum creatinine, but with some early impairment of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine it was increased in patients with normal serum creatinine, but with some early impairment of renal function. The authors suggested that this metabolite may be utilized as a future biomarker for early stages of CKD [ 44 ]. We observed a strong correlation between glutamic acid accumulation and the second stage of CKD in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar da possibilidade de outra via ser estimulada para gerar ATP, a doença renal crônica é uma enfermidade que resulta em diminuição da oxidação de ácidos GAYAR et al, 1994;SULIMAN et al, 2005) Já a ureia, molécula filtrada pelos glomérulos e parcialmente reabsorvida pelos túbulos proximais e distais, também é um dos biomarcadores mais afetados quando há redução na TFG (DOSSETOR, 1966;PARK;RABINOWITZ, 1969;BRAUN;LEFEBVRE, 2008;KOBAYASHI, 2015). Porém, é válido relembrar que esta é uma molécula sintetizada no fígado e que além disso pode ser influenciada pela desidratação, desnutrição, estado de catabolismo proteico, teor de proteína da dieta, utilização de glicocorticoide, além de sangramento gastrintestinal.…”
Section: Variávelunclassified